Implementation Of Lean Tool For Process Improvement Of Banking Services: A Case Study Of Regional Banks - Muchamad Nurdin Alwi; Lien Herliani Kusumah (Jurnal Manajemen Industri dan Logistik, 2022)
Bank BJB continues to improve service quality by developing and strengthening banking services to customers. The current problems faced by Bank BJB are delays in service processes where the actual processing time exceeds the Service Level Agreement (SLA). The delay in the process is a non-value-added activity which is called waste. Aim This research aims to identify critical business processes of banking services that cause waste and improve using the Business Process Improvement method in the BJB Regional Treasury Branch. The research used the match method, data collection were obtained observation, interviews, and brainstorming with top management and users. Improvement using BPI was able to reduce the waiting time (queue) as waste and reduce lead time. The results of this study show the need for improvements to the tasks and functions of some parts such as Operational Service Officer, and Credit Officer so that more editions and no waste of time. So that the quality of service and customer satisfaction is achieved